2020
DOI: 10.1007/s13524-020-00892-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Education on Mortality: Evidence From Linked U.S. Census and Administrative Mortality Data

Abstract: Does education change people’s lives in a way that delays mortality? Or is education primarily a proxy for unobserved endowments that promote longevity? Most scholars conclude that the former is true, but recent evidence based on Danish twin data calls this conclusion into question. Unfortunately, these potentially field-changing findings—that obtaining additional schooling has no independent effect on survival net of other hard-to-observe characteristics—have not yet been subject to replication outside Scandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 84 publications
3
29
0
1
Order By: Relevance
“…Nearly uniformly, more schooling is found to equal better health (Cutler and Lleras-Muney 2008; Zajacova and Lawrence 2018). At least some of education’s effects on health are causal (Eide and Showalter 2011; Fletcher 2015; Halpern-Manners et al 2020; Lleras Muney 2005). The mechanisms through which education impacts health are so numerous that education has been conceptualized as a fundamental cause (Link and Phelan 1995) or a metamechanism (Freese and Lutfey 2011) influencing health.…”
Section: Postsecondary Education and Health Outcomesmentioning
confidence: 99%
“…Nearly uniformly, more schooling is found to equal better health (Cutler and Lleras-Muney 2008; Zajacova and Lawrence 2018). At least some of education’s effects on health are causal (Eide and Showalter 2011; Fletcher 2015; Halpern-Manners et al 2020; Lleras Muney 2005). The mechanisms through which education impacts health are so numerous that education has been conceptualized as a fundamental cause (Link and Phelan 1995) or a metamechanism (Freese and Lutfey 2011) influencing health.…”
Section: Postsecondary Education and Health Outcomesmentioning
confidence: 99%
“…The positive relationship between own education and health is well established and nearly universally observed (Mirowsky and Ross 2003). Studies show that people with more schooling tend to experience better overall health (Lynch and von Hippel 2016; Mirowsky and Ross 2003; Ross and Wu 1995), fewer chronic conditions (Matthews et al 1989; Maty et al 2005; Winkleby et al 1992), more successful aging (Montez and Hayward 2014), and an increased chance of survival (Halpern-Manners et al 2020; Hummer and Hernandez 2013) compared to those with lower levels of education. These findings have been documented across a broad range of social, institutional, and policy contexts (Mackenbach et al 2008; Montez et al 2019) and have been shown to hold (to varying degrees) by race-ethnicity (Hummer and Lariscy 2011), gender (Ross and Mirowsky 2006), age (Lynch 2003), and birth cohort (Lauderdale 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, this is akin to finding two people who look alike across a range of relevant dimensions but whose spouses differ with respect to educational attainment—and then asking whether there are consequences for their health. Similar procedures have been used in the past to identify the effects of own education on health and longevity (Amin, Behrman, and Kohler 2015; Halpern-Manners et al 2020), but applications to the question of crossover effects have been rare (Amin et al 2015).…”
mentioning
confidence: 99%
“…Education reduces the mortality rate by increasing consciousness and responsiveness, as explicated in a number of empirical works, for example Halpern-Manners et al [ 10 ], Doniec et al [ 34 ], Buckles et al [ 33 ], Sajedinejad et al [ 35 ], Ray and Linden (2020), Alemu [ 8 ], Farahani et al [ 25 ], among others. Halpern-Manners et al [ 10 ] observed the robust relationships between education and mortality in the case of the USA. Similarly, Doniec et al [ 34 ] discerned that those in lower educational groups were significantly more likely to die in the case of 3 Eastern European countries covering the period of 1982–2013.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adequate and sufficient sanitation facilities also play a significant role in improving human health and reducing the mortality rate by maintaining safety and hygiene [ 8 , 14 16 , 27 , 30 – 32 ]. In the same way, education facilities help to increase awareness about health consciousness and this may play a role in lowering the death rate ([ 10 , 33 35 ]; Ray and Linden, 2020 [ 8 , 25 ];). While a greater urbanisation rate increases different health related amenities which reduces mortality rate on the one hand, it also increases mortality by increasing pollution due to different urban activities ([ 9 , 16 , 17 , 32 , 36 , 37 ]; and [ 27 ]).…”
Section: Introductionmentioning
confidence: 99%